2021
DOI: 10.4018/ijamc.290534
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Particle Swarm and Ranked Firefly Metaheuristic Optimization-Based Software Test Case Minimization

Abstract: Software testing is a valuable and time-consuming activity that aims to improve the software quality. Due to its significance, combinatorial testing focuses on fault identification by the interaction of small amount of input factors. But, deep testing is not sufficient due to time or resources availability. To select the optimal test cases with least computation time, Hybrid Multi Criteria Particle Swarm and Ranked Firefly Metaheuristic Optimization(HMCPW-RFMO) technique are introduced. Initially, the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, the alternative version of the dragonfly algorithm must be explored to enhance the DAPSO performance. Similarly, Bharathi [140] presented a hybrid approach called hybrid multi criteria particle swarm and ranked firefly meta-heuristic optimisation (HMCPW-RFMO) to solve multi-objective problems for combinatorial software testing. HMCPW identifies the local best solution among the number of test cases, while the combination with RFMO identifies the global best solution.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the alternative version of the dragonfly algorithm must be explored to enhance the DAPSO performance. Similarly, Bharathi [140] presented a hybrid approach called hybrid multi criteria particle swarm and ranked firefly meta-heuristic optimisation (HMCPW-RFMO) to solve multi-objective problems for combinatorial software testing. HMCPW identifies the local best solution among the number of test cases, while the combination with RFMO identifies the global best solution.…”
Section: Studymentioning
confidence: 99%
“…Three studies focus on path coverage [137,138,142], two studies deal with code coverage [122,132], and two studies employ branch coverage criteria [129,133]. Finally, some studies focussed on requirement coverage [15], twise coverage [123], mutation score [129], line coverage and MC/DC [134], and pairwise coverage [140].…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the hybrid of PSO with Gravitational Search Algorithm (PSOGSA) outperformed GA, PSO and GSA [5]. The test suite was minimized using hybrid PSO and the Firefly Algorithm, considering the fault coverage [19]. The modified condition decision coverage criteria were employed as fitness measures in PSO for prioritizing the test cases [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this process, attention should be paid to the need to operate the equipment in strict accordance with the relevant national standards to avoid unnecessary or non-conformance to the requirements of national standards, which may cause water quality safety problems. The second is to take measures against those water bodies that cannot meet the national discharge standards and requirements and are polluted by corrosive water pollution sources [15][16].…”
Section: Figure 1 Water Pollution Prevention and Control Project Processmentioning
confidence: 99%